2020
DOI: 10.14814/phy2.14489
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity exercise stimulates bioenergetics and increases fat oxidation in mitochondria of blood mononuclear cells from sedentary adults

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…There are also findings that people with a single nucleotide polymorphism in the NDUFB6 gene encoding a subunit of mitochondrial complex I do not respond to exercise by improving insulin sensitivity and glucose homeostasis [ 76 ], which is direct evidence that mitochondria are critical for exercise benefits in diabetes. Low-intensity exercises in healthy volunteers with a sedentary lifestyle increased PBMCs ROUTINE respiration, LEAK and OXPHOS with fatty acid substrates-dependent respiration by 31%, 65%, and 76%, respectively [ 77 ]. In addition, during 60 min of low-intensity exercise, a 2-fold higher lipolysis rate was observed, and 57% more fat was metabolized than during the incremental-load exercise [ 77 ].…”
Section: Interventions Targeting Mitochondria In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also findings that people with a single nucleotide polymorphism in the NDUFB6 gene encoding a subunit of mitochondrial complex I do not respond to exercise by improving insulin sensitivity and glucose homeostasis [ 76 ], which is direct evidence that mitochondria are critical for exercise benefits in diabetes. Low-intensity exercises in healthy volunteers with a sedentary lifestyle increased PBMCs ROUTINE respiration, LEAK and OXPHOS with fatty acid substrates-dependent respiration by 31%, 65%, and 76%, respectively [ 77 ]. In addition, during 60 min of low-intensity exercise, a 2-fold higher lipolysis rate was observed, and 57% more fat was metabolized than during the incremental-load exercise [ 77 ].…”
Section: Interventions Targeting Mitochondria In Diabetesmentioning
confidence: 99%
“…Low-intensity exercises in healthy volunteers with a sedentary lifestyle increased PBMCs ROUTINE respiration, LEAK and OXPHOS with fatty acid substrates-dependent respiration by 31%, 65%, and 76%, respectively [ 77 ]. In addition, during 60 min of low-intensity exercise, a 2-fold higher lipolysis rate was observed, and 57% more fat was metabolized than during the incremental-load exercise [ 77 ]. High intensity interval training increased electron transfer (ET) capacity (respiration in the presence of uncoupler) in muscle of T2D patients and controls, irrespective of IR [ 78 ].…”
Section: Interventions Targeting Mitochondria In Diabetesmentioning
confidence: 99%
“…Unsurprisingly, whole-body prolonged exercises resulted in post-exercise increases in FAO products, and decreases in plasma triacylglycerol esters and phospholipids have been observed in athletes [ 96 , 97 ]. Most recently, a study also showed low-intensity exercise was able to improve mitochondrial oxidative bioenergetics and increased FAO in peripheral blood mononuclear cells (PBMCs) in sedentary individuals [ 98 ].…”
Section: Exercise As a Regulator Of Immunometabolismmentioning
confidence: 99%
“…Irisin has also been found to favourably alter genes in adipocytes that are affected by the SARS-CoV-2 [ 19 ] and to modulate macrophage reactive oxygen species (ROS), displaying anti-oxidant and anti-inflammatory properties [ 20 ]. Critically, exercise can enhance mitochondrial function and capacity in peripheral blood mononuclear cells (PBMCs) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%